Pengaruh Beban Kerja, Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT JNE Bekasi - Dyah Ayu Saputri; Jumawan; Fahmi Sahlan (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
The effect of Beban Kerja, Disiplin Kerja and Kepuasan Kerja on Kinerja Karyawan is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. The results of this article: 1) Beban Kerja has an effect on Kinerja Karyawan; 2) Disiplin Kerja has an effect on Kinerja Karyawan; and 3) Kepuasan Kerja has an effect on Kinerja Karyawan.